A prisão temporária e a instrumentalidade material do processo: os reflexos jurídico-políticos do julgamento das ADIs n. 3361 e n. 4109 - Pereira, Gibran Pedro (2024)
This dissertation is part of the Research Line Social Relations and Dimensions of Power, with the theme of temporary imprisonment and the decision of the STF in ADIs 3360/DF and 4109/DF and the material instrumentality of the process. The theme is based on the following problem: What are the possible legal-political consequences of the decision, by the Supreme Federal Court in ADIs no. 3360 and no. 4109, of temporary imprisonment in view of the principle of material instrumentality of the process? The general objective is to analyze the decisions of the ADIs in view of the constitutionality and material instrumentality (a) to develop the study of the power relations that shape society, instrumentality and guaranteeism; (b) to analyze the contempt of guarantee of public order (c) to verify the decision of the STF and its possible legal-political consequences. The basic concept used was Ferrajoli's guarantee theory. Through the deductive method, it was possible to conclude that despite the decisions of the STF and Law 12.403/2011, the practical reality indicates that temporary imprisonment will continue to be used extensively, often as a response to social pressures for security, rather than being a last resort, as advocated by the guarantor theory. This reflects the need for a continuous effort to align theory and practice in the criminal justice system, considering the challenges associated with changing ingrained judicial practices and the mindset of legal practitioners.